Pitting Corrosion and Stress Corrosion Cracking Study in High Strength Steels in Alkaline Media - Venegas-Toledo, R (Springer New York LLC, 2016)
Steel reinforcement in concrete is protected from corrosion by passivation due to the high alkalinity of the cement pore solution, but the presence of aggressive ions as Cl− could induce pitting corrosion processes thus decreasing the durability of the structure. This also occurs for prestressing concretes but the risk to suffer pitting corrosion in presence of aggressive ions, and hence stress corrosion cracking (SCC), increases due to the external mechanical load. The study of the corrosion processes by classical methods involves the determination of pitting potential (Epit) or the polarization resistance monitoring during long periods (icorr). However, the large number of parameters, which could potentially influence the determination of the Epit or the icorr values, result in a great variety of results in literature. The present study proposes a simple and reliable method to evaluate the susceptibility to suffer pitting corrosion process and stress corrosion cracking by the induction of pitting corrosion process by cyclic voltammetry. The pitting corrosion intensity is evaluated by means of the charge during the corrosion process, and related with the weight loss and the decrease of the mechanical properties of the steel under external load. The results show a linear and a volcano trend when pitting corrosion process and stress corrosion cracking are respectively evaluated. © 2015, Springer-Verlag Berlin Heidelberg.